Reduced Nutrient Excretion and Environmental Microbial Load with the Addition of a Combination of Enzymes and Direct-Fed Microbials to the Diet of Broiler Chickens - Praes, M. F. F. M. [UNESP]; Lucas Junior, J. [UNESP]; Duarte, K. F. [UNESP]; Sorbara, J. O. B.; Matos Junior, J. B. [UNESP]; Sgavioli, S.; Domingues, C. H. F.; Garcia, R. G.; Hermes, R. G. (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2016)
This study evaluated the effects of the dietary inclusion of an enzyme blend and a direct-fed microbials in broiler diets on litter production and quality. In total, 900 Cobb 500 (R) broiler chicks were distributed according to a completely randomized design into 4 treatments and 9 replicates of 25 birds each. Broilers were reared from 1 to 42 days of age. The treatments consisted of the following diets: NC: negative control; DFM: NC + 500 ppm of direct-fed microbials product (DFM), containing Bacillus subtilis and Bacillus licheniformis; ENZ: diet formulated with an enzyme blend (20 ppm phytase, 200 ppm protease and 200 ppm of xylanase); DFM+E: ENZ + DFM. Birds and litter were weighed at the start and end of the rearing period, for litter production and waste ratio (Rw) determination. Litter samples were analyzed for dry matter (DM) content, total and thermotolerant coliform counts, nutrient composition (nitrogen (N), phosphorous (P) and potassium (K)), and fiber fraction (neutral detergent fiber (NDF), acid detergent fiber (ADF) and lignin). The dietary inclusion of the evaluated additivesdid not influence litter production or Rw; however, ADF (%), NDF (kg and kg/kg DM litter), and total and thermotolerant coliform counts were reduced, and N content increased in the litter. The diets containing enzymes (ENZ and DFM+ E) reduced litter P content. The addition of exogenous enzymes and their combination with a DFM based on Bacillus spp. Did not affect waste production, and reduced litter microbial load, and the contents of P and insoluble fiber in the litter.
Keywords: Waste ratio; total and thermotolerant coliforms; phosphorus; nitrogen; potassium